MRI Characteristics of the Evolution of Supratentorial Recent Small Subcortical Infarcts - Okazaki, Shuhei; Hornberger, Eva; Griebe, Martin; Gass, Achim; Hennerici, Michael G.; Szabo, Kristina (Frontiers in Neurology, 2015)
Objective: Morphological changes of recent small subcortical infarcts are not well defined. The purpose of the present study was to describe the MRI characteristics of the evolution for this stroke subtype. Methods: We conducted a retrospective review of patients diagnosed with definite supratentorial recent small subcortical infarcts according to the ASCO classification with baseline and follow-up MRI (≥ 90 days of stroke onset). We investigated the incidence of cavity formation, the infarct volume change, and the positional relationship between infarct lesions and preexisting white matter hyperintensities of presumed vascular origin (WMHs). Results: We identified 62 patients with a median age of 71 years (range: 30 – 87). Median follow-up period was 26 months (range: 3 – 99). Cavity formation was observed in 38 infarct lesions (61%). Eighteen lesions (29%) were partially adjacent to WMHs and 7 (11%) were fused into WMHs. In a multiple logistic regression analysis, age (odds ratio per 5-year increase: 1.34; 95% confidence interval (CI): 1.03 – 1.80; p = 0.03) and baseline infarct volume (odds ratio per 1-ml increase: 4.7; 95% CI: 1.6 – 19.7; p = 0.003) were independent predictors of cavity formation. There was a significant volume reduction between baseline and follow-up infarct lesions (median volume reduction rate: 44%). Conclusions: More than one third of recent small subcortical infarcts do not lead to cavity formation and 40% of infarct lesions overlap with WMHs. Our data indicate the continuity between recent small subcortical infarcts and WMHs.